2014
DOI: 10.18632/oncotarget.2342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical multiplexed exome sequencing distinguishes adult oligodendroglial neoplasms from astrocytic and mixed lineage gliomas

Abstract: Classifying adult gliomas remains largely a histologic diagnosis based on morphology; however astrocytic, oligodendroglial and mixed lineage tumors can display overlapping histologic features. We used multiplexed exome sequencing (OncoPanel) on 108 primary or recurrent adult gliomas, comprising 65 oligodendrogliomas, 28 astrocytomas and 15 mixed oligoastrocytomas to identify lesions that could enhance lineage classification. Mutations in TP53 (20/28, 71%) and ATRX (15/28, 54%) were enriched in astrocytic tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 27 publications
(26 reference statements)
2
50
0
Order By: Relevance
“…In the past, there has been considerable inconsistency in diagnostic criteria for oligoastrocytomas, and many LGGs with "ambiguous morphology" received this diagnosis. [8][9][10] Our results indicated that…”
Section: Commentarymentioning
confidence: 52%
“…In the past, there has been considerable inconsistency in diagnostic criteria for oligoastrocytomas, and many LGGs with "ambiguous morphology" received this diagnosis. [8][9][10] Our results indicated that…”
Section: Commentarymentioning
confidence: 52%
“…The immunohistochemical evaluation of the ATRX protein expression could represent an alternative method to assess the ATRX status. Although studies reported concordant results between the mutation analysis and IHC [38,72], tumor heterogeneity in the ATRX expression and concurrent normal non-tumor cells with constitutive ATRX expression may explain possible discrepancy. As a matter of fact, ATRX mutations/ATRX protein loss characterizes astrocytic gliomas, whereas retained ATRX immunoreactivity characterizes oligodendroglial gliomas.…”
Section: Atrx Mutationsmentioning
confidence: 95%
“…Restricted to IDH mutant tumors, they are significantly associated to TP53 mutations and nuclear p53 overexpression and to astrocytic differentiation; they are mutually exclusive with 1p/19q co-deletion [71,72]. ATRX and IDH1/2 mutations occur in association and they may represent early genetic alterations in the development of gliomas affecting progenitors before their differentiation along the two lineages.…”
Section: Atrx Mutationsmentioning
confidence: 99%
See 2 more Smart Citations